The Effectiveness of Using Multimedia in Teaching Islamic Jurisprudence of Sixth Primary Students, and its Impact on Academic Attainments and Students’ Attitudes towards it. - Al-Faqih, Abdullah bin Ibrahim (Arab Journal for Sciences and Research Publishing, 2015)
Aim of the Study: This research aimed at knowing the effectiveness of using multimedia on both academic attainments, and developing the attitude towards the Islamic Jurisprudence of sixth primary students. Assumptions of the Research: The research selected the following assumptions: There are not statistical significant differences at (0.05) level between the averages of the scores of pre and post academic attainments of the experimental and control group. There are not statistical significant differences at (0.05) level in academic attainments between the experimental and control group. There are statistical significant differences at (0.05) level between the students’ average scores on the scale of the pre attitude and between the students’ average scores on the scale of the post attitude of the control group. Procedures of the Research: The researcher has used the quasi experimental method, The research has been applied on a sample of( 34) students. These students have been divided into two groups; control group with (17) students, and experimental group with (17) students. The Used Statistical Methods: The researcher has used Holistic equation in order to measure the reliability of content analysis. Also, he used Kuder-Rishadr Son equation and Qausi division method to measure the reliability of the academic attainments test. Furthermore, he used Alpha Cronpah equation to measure the reliability of the attitude scale. Finally, he used T-test. The Most Important Results of the Study: There are statistical significant differences between the scores’ average of the post test among the students of the experimental group and the control group. The result is for the sake of the experimental group. There are statistical significant differences between the scores’ average of the pre and post test of the experimental group, for the sake of the post test. There are statistical significant differences between the scores’ average of post scale of the control group, for the sake of the experimental group.